ETIKA PENDIDIKAN: MENANAMKAN NILAI-NILAI MORAL DALAM SISTEM PENDIDIKAN MODERN - virdaus, varia virdania; Lestari, Gunarti Dwi; Susilo, Heryanto (MOTORIC, 2025)
Moral education is a crucial element in building a generation with character, especially amid the challenges of social change and globalization. This article analyzes the importance of ethics in education with a philosophical and qualitative approach, focusing on the concept, theory, and practical application of moral values in the modern education system. The philosophical approach uses ethical theories, namely deontology, utilitarianism, and virtue ethics, to explore the relationship between moral principles and educational practices. The qualitative approach involves analysis of primary and secondary literature and contextual case studies. The results of the analysis show that moral education can improve interpersonal relationships in the school environment, shape socially responsible students and create an inclusive society. Strategies for implementing moral values include integration in the formal curriculum, extracurricular programs and the role of teachers as moral role models. However, obstacles identified include the lack of teacher training, the dominance of academic orientation in the education system and the challenges of multiculturalism. This article recommends educational reforms that emphasize value-based curriculum, intensive teacher training, and holistic measurement of success to balance cognitive and moral aspects. With the integration of ethics, the education system can shape individuals who are not only skilled but also have high moral integrity.This conclusion emphasizes the importance of moral education as the core of the modern education system, making it the main tool in creating a moral and welfare-oriented future generation. This article makes theoretical and practical contributions to the development of value-based education in the era of globalization. Keywords: educational ethics, moral values, modern education, ethical theory, character education